Glass-formation region of ternary Sn-Sb-Se-based chalcogenide glasses - Adam, A. B.; Sakrani, Samsudi; Wahab, Y. (Springer Netherlands, 2005)

(untitled)
Tin-antimony-selenium (TAS)-based system belongs to the ternary chalcogenide compounds of IV-V-VI group owing to their heavy elemental masses, their glass formation region was assumed to be small comparing to their counterpart elements in the same group. However, there were rare published reports on their glass structure, while their glass boundary formation region was not yet reported. It was the aim of this paper to map their glass-forming region experimentally using XRD and validate it theoretically using the average co-ordination number, Î¼, and the fraction of the bond distributions, f, from chemical order model. Theoretically, it was validated that the glass formation was arrested between Î¼ â‰¤ 2.4 and the fraction of Sn-Se bonds, f sn-se < 44.5%. XRD analyses of 66-as-prepared samples revealed that the glass formation region was located within the predicted area that mapped in structural triangle.